Örök jelen(lét)re kárhoztatva: Az újrafordítás néhány kérdése az antik versfordítás viszonylatában - Csehy, Zoltán (Studia Litteraria, 2024)
This paper presents some strategies for re-translation in the ancient context. First, I examin a series of attempts at re-translation arising from a critical relation to tradition. The starting point was Ponori Thewrewk’s translation of Simonides’ epigram, whose canonical position remains unshaken to this day, despite new attempts at translation. Next comes a fetishising example of the relationship to the literary translation tradition, the 19th century translation of Horace by János Arany (Carm. 2.8). Despite the fact that Arany’s translation does not retain the poetic form of the original Horace poem and its poetic solutions are now alien, and it cannot be held up as a literary translation example for modern literary translators, it has been handed down from anthology to anthology with astonishing success. The next problem is the special fusion of re-translation and adaptation techniques. I capture this phenomenon through Vince Földiák’s translation of Horace. Finally, some alternative strategies of retranslation is discussed, such as queering the text or acoustic translation.